2022
DOI: 10.1155/2022/3339866
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Ultrasonography as a Tool for Monitoring Disease Activity in Patients with Ulcerative Colitis

Abstract: Background. Ultrasonography is a noninvasive, inexpensive, and widely available diagnostic tool. In the last two decades, the development of ultrasound techniques and equipment has significantly increased the usage of intestine ultrasound (US) in the assessment of the gastrointestinal tract in patients with inflammatory bowel disease (IBD). Although current guidelines suggest routine utilization of US in patients with Crohn’s disease, data regarding US usage in ulcerative colitis are still scarce. We aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This is especially true as there are limitations on how quickly endoscopy can occur due to logistical reasons, such as patient preference, timing, availability, and fasting status. The utilization of IUS has been proposed as a valuable means for screening IBD, particularly in evaluating the anatomical extent of CD at initial diagnosis [ 33 , 34 ]. A previous meta-analysis investigating the diagnostic accuracy of IUS in identifying active CD reported combined sensitivity and specificity rates of 88% and 97%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true as there are limitations on how quickly endoscopy can occur due to logistical reasons, such as patient preference, timing, availability, and fasting status. The utilization of IUS has been proposed as a valuable means for screening IBD, particularly in evaluating the anatomical extent of CD at initial diagnosis [ 33 , 34 ]. A previous meta-analysis investigating the diagnostic accuracy of IUS in identifying active CD reported combined sensitivity and specificity rates of 88% and 97%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroenterology Review the presence of severe ulcerative colitis that is actively developing [29]. The TRUST-UC trial is the broadest multicentre investigation concerning the application of intestinal ultrasound in patients with UC; in this study, BWT was verified as a US parameter for the identification of disease activity [30].…”
Section: Sensitivitymentioning
confidence: 97%
“…BWT, CDS, and loss of BWS are also used in UC to assess disease activity. Of these, the BWT is the most strongly correlated with endoscopic findings [41,[81][82][83]. Although 3 mm is considered the minimum value for an abnormal colon wall [54,84], statistical analysis in different studies has found different cut-offs with variate sensitivities and specificities (Table 6) [26,85,86].…”
Section: Disease Activity Evaluationmentioning
confidence: 99%
“…In contrast, mesenteric fat hypertrophy, lymph nodes, loss of BWS, and loss of haustration showed only a fair agreement. The severity also depends on the IUS parameters, with higher disease activity exhibiting an increased risk of surgery [82,83,87]. Segmental accuracy is superior for IUS in the ascending and right colon, while CS can be used to assess the rectum [5,92].…”
Section: Disease Activity Evaluationmentioning
confidence: 99%